Cell fate in plants. Lessons from the Arabidopsis root. - Dolan, L; Linstead, P; Kidner, C; Boudonck, K; Cao, X; Berger, F (1998)
Classical studies in plant development have indicated that the fate of plant cells is fixed late, after cell division has ceased. Earlier commitment events are therefore considered reversible. To gain a mechanisatic understanding of the processes involved in specification and fixation of cell fate in plants, we are using the Arabidopsis root epidermis as a model system. The Arabidopsis root epidermis is composed of two cell types whose pattern of differentiation is directed by positional cues during development. Examination of mutations has identified genes involved in the establishment of cell fate specification in this tissue. TRANSPARENT TESTA GLABRA (TTG) and GLABRA2 (GL2) are positive regulators of non-hair fate and are active during the early differentiation of the epidermis in the meristem. GL2 encodes a homeobox protein which is expressed in non-hair cells in the meristem and is positively regulated by TTG. Mutations in genes involved in the regulation of ethylene biosynthesis and signal transduction indicate that ethylene is a positive regulator of hair cell fate. Treatment of ttg and gl2 plants with modulators of ethylene biosynthesis indicate that ethylene acts down stream of TTG and GL2 during the fate specification process. The relationship between meristem organisation and the mechanism underpinning the establishment of cell fate in other systems is also discussed.